Corporate risk tolerance assessment and its application on optimal working interest : the case of E&P industry in Thailand - Nantaphat Chotsubyodchana; Chiu, Gregory L.F.; Thitisak Boonpramote; Widjaja, Joko Harsono; Royal Thai Government (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
This study presents a measure of corporate risk taking that conforms to the behavior of the decision makers which have concern with notion of risk in the petroleum E&P firm in Thailand. The two group of respondent is required to asses the important main parameters which are risk tolerance and consistency measure are the manager levels who have a authority making a decision and technical levels who never experience in decision making. The questionnaire is designed based on concept of risk aversion and it consists of ten risky prospects which have different between NPV and the probability. Moreover, this study illustrates how to select the optimal working interest in any projects while the traditional method can not suggest the most suitable choice in the risky condition. The results of this study illustrate that the manager levels are less risk averse and more consistent in terms of financial risk taking due to their experience for decision making and the corporate risk tolerance is set from $76 to $86 million. This values are the created the well-communication between the decision makers to better understanding the business strategies for the company. In addition, the preference theory suggests that the company should invest in three projects with 37%,41 % and 58% working interest respectively, whereas the traditional approach suggests that it should incur only 100% working interest on order to get the maximum profit, on the other hand, in failure, it will loss at maximum.
A thesis proposal submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Offshore Technology and Management, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Energy industries -- Risk assessment -- Thailand; Risk assessment -- Thailand